Teacher emotionally intelligent behaviors and its role in the link between cybervictimization and suicide risk factors in adolescents - Mérida-López, Sergio; Quintana-Orts, Cirenia Luz; Gómez-Hombrados, Jorge; Extremera, Natalio (Elsevier, 2024)
Psychological distress is an increasing concern among adolescents worldwide. Cybervictimization is con-sidered one of the stressors that adolescents may face, and it signiﬁcantly impacts various indicators of suicide risk (i.e., symptoms of depression, anxiety, and stress, and suicidal ideation). However, teacher emotionally intelligent behaviors (TEIB) might mitigate the links between cybervictimization experiences and suicide risk factors. This study aimed to examine the relationships between cybervictimization and several suicide risk indicators, as well as the potential moderating role of TEIB in these links. A sam-ple of 1,866 (996 girls) adolescents (Mage = 13.99, SD = 1.44) participated in this study and completed widely validated measures. Moderation analyses revealed that TEIB moderated the positive associations between cybervictimization and symptoms of depression, anxiety, and stress, even after controlling for the effects of sociodemographic factors (i.e., age and gender) and emotional intelligence. However, TEIB did not moderate the link between cybervictimization and suicidal ideation. These novel ﬁndings both underscore the signiﬁcance of students’ perceptions of TEIB in shaping their psychological well-being and highlight potential avenues for research aimed at mitigating the consequences of cybervictimization.
Keywords: Adolescentes; Suicidio; Educación; Cibervictimización; Factores de riesgo de suicidio; Adolescentes; Comportamientos emocionalmente inteligentes docentes; Educación